SISTEM INFORMASI ADMINISTRASI PEMBAYARAN BERBASIS APLIKASI WEB STUDI KASUS PADA SMK AL-WAHDAH CITERAS SERANG-BANTEN - Khasan Asrori; Ely Nuryani (Program Studi Sistem Informasi, Universitas Banten Jaya, 2020)
The research outlined in this title aims to design a system that can facilitate the payment administration process. The research method used is descriptive research method. Descriptive method is a method of researching an object that aims to make a description, picture or painting in a systematic, factual and accurate manner about the facts, properties and relationships between the phenomenon under investigation. And the Waterfall system design method which in this method has the stages of Planning, Requirement Analysis, Design, Implementation, Testing and Documentation. Finally, after analysing and discussing the problem, it was concluded that a more flexible payment administration system was needed for SMK Al-Wahdah. Due to the existing system at Al-Wahdah Vocational School, there is a lot of damage and it is not flexible